PURCHASE INTEREST MEDIATES THE INFLUENCE OF SOCIAL MEDIA, PRICE PERCEPTION, SERVICE QUALITY ON PURCHASE DECISIONS (Case Study on Consumers of CV Catering Nyonya Warti Buleleng) - I Gusti Ayu Agung Mitha Saritha Dian Ajnya; Putu Dyah Permatha Korry (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the role of purchase intention in mediating the influence of social media, price perception, and service quality on purchasing decisions at CV Catering Nyonya Warti Buleleng. The research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through online questionnaires distributed to 150 consumers of CV Catering Nyonya Warti Buleleng in Denpasar City using purposive sampling techniques. The variables examined in this study include social media, price perception, service quality, purchase intention, and purchasing decisions. The results reveal that service quality and price perception have a positive and significant effect on purchase intention, while social media does not significantly affect purchase intention. Furthermore, purchase intention has a positive and significant influence on purchasing decisions. The mediation analysis indicates that purchase intention significantly mediates the relationship between service quality and purchasing decisions, as well as between price perception and purchasing decisions. However, purchase intention does not mediate the relationship between social media and purchasing decisions. These findings suggest that service quality and price perception are essential factors in increasing consumer purchase intention and purchasing decisions in the catering business sector. The study contributes to the development of consumer behavior theory and provides managerial implications for MSMEs in designing effective marketing strategies in the digital era.